Hydriding/dehydriding properties of Mg-Ni-based ternary alloys synthesized by mechanical grinding - 陈玉安 杨丽玲 林嘉靖 程绩 潘复生 (Transactions of Nonferrous Metals Society of China, 2010)
The Mg-Ni-based ternary alloys Mg2-xTixNi（x=0,0.2,0.4）and Mg2Ni1-xZrx（x=0,0.2,0.4）were successfully synthesized by mechanical grinding.The phases in the alloys and the hydriding/dehydriding properties of the alloys were investigated.Mg2Ni and Mg are the main hydrogen absorption phases in the alloys by XRD analysis.Hydriding kinetics curves of the alloys indicate that the hydrogen absorption rate increases after partial substitution of Ti for Mg and Zr for Ni.According to the measurement of pressure-concentration-isotherms and Van’t Hoff equation,the relationship between ln p（H2）and 1 000/T was established.It is found that while increasing the content of correspondingly substituted elements at the same temperature,the equilibrium pressure of dehydriding increases,the enthalpy change and the stability of the alloy hydride decrease.